Veterinary microbiology - Chengappa, M. M.; McVey, D. Scott; Wilkes, Rebecca; Kennedy, Melissa (Melissa Anne) 1959- (Hoboken, New Jersey Wiley, 2022)
Veterinary Microbiology, Fourth Edition presents comprehensive information based on the most recent research, diagnostic, and clinical publications for bacterial, fungal, and viral animal diseases. The information provided is intended to be most relevant for veterinary students and practitioners. The text is supported throughout by high-quality and full-color images to aid learning. A companion website offers chapter content, supplemental information, and figures from the book in PowerPoint format. Pathogenic bacteriology: includes major classifications and genera of bacteria associated with veterinary infectious disease Pathogenic mycology: dermatophytes, agents of subcutaneous mycoses, and agents of systemic mycoses Pathogenic virology: includes RNA and DNA viruses as well as prions associated with veterinary infectious disease"--
Includes bibliographical references and index.
Description based on print version record and CIP data provided by publisher; resource not viewed.
Keywords: Animals -- Diseases -- Microbiology; Microbiology -- Research; Veterinary medicine; Animal health surveillance -- Microbiology